Ask again, yes eaudiobook A novel. - Keane, Mary Beth (Simon & Schuster Audio, 2019)
The triumphant New York Times Bestseller *The Tonight Show Summer Reads Pick* Named one of the Best Books of the Year by People , Vogue , Parade , NPR, and Elle "A gem of a book." — Taylor Jenkins Reid, author of The Seven Husbands of Evelyn Hugo How much can a family forgive? Francis Gleeson and Brian Stanhope, rookie NYPD cops, are neighbors in the suburbs. What happens behind closed doors in both houses—the loneliness of Francis's wife, Lena, and the instability of Brian's wife, Anne, sets the stage for the explosive events to come. In Mary Beth Keane's extraordinary novel, a lifelong friendship and love blossoms between Kate Gleeson and Peter Stanhope, born six months apart. One shocking night their loyalties are divided, and their bond will be tested again and again over the next thirty years. Heartbreaking and redemptive, Ask Again, Yes is a gorgeous and generous portrait of the daily intimacies of marriage and the power of forgiveness.